Transforming crime victims’ rights: from myth to reality - Cassell, Paul (International journal of comparative and applied criminal justice, 2021)
Rights for crime victims have been decried as myths; entitlements that have little enforceability. At the same time, they have been criticised as undermining the legal rights of the accused person. In this Guest Editors Introduction to the Special Issue, Making Rights Real, we suggest that victims’ rights are in transition. Rights may be set out in legal instrument but, we argue, it is through the practices of people in their myriad settings that are part of that shift to realising rights in action. We describe ways in which we see victims’ rights being realised in different parts of the world and develop a human rights framework for the rights of crime victims to further shape the transition.